Partial PFO Closure for Persistent Hypoxemia in a Patient with Ebstein Anomaly - S. A. Zuberi; S. Liu; J. W. Tam; F. Hussain; D. Maguire; M. Kass (Case Reports in Cardiology)
Ebstein anomaly is characterized by deformities of the anterior leaflet of the tricuspid valve and atrialization of the right ventricle. Patients with severe tricuspid regurgitation are recommended to have tricuspid valve surgery with concomitant atrial septal defect closure. A 73-year-old female with Ebstein anomaly presented with severe hypoxemia. Transthoracic echocardiography revealed severe tricuspid regurgitation and a patent foramen ovale with right-to-left shunting. Complete percutaneous patent foramen ovale closure led to acute decompensation; however, partial closure led to hemodynamic stability and improved oxygenation. In conclusion, similar patients with “patent foramen ovale dependency” from longstanding shunts may benefit from partial patent foramen ovale closure.